Persepsi dan Motivasi Belajar Mahasiswa Angkatan 2019 tentang Proses Pembelajaran di Fakultas Kedokteran Universitas Pattimura Ambon - Astina Astina; Parningotan Y. Silalahi; Yuniasih MJ. Taihuttu; Ony W Angkejaya (Journal on Education, 2023)
Perception is a person's ability to organize an observation, these abilities include: the ability to differentiate, the ability to group, and the ability to focus. Motivation is an effort that encourages individuals to engage in certain behaviors in an effort to achieve goals. In general, motivation can be interpreted as an internal process that is influenced by the right stimulus, causing activity that is more intense than usual. This study aims to determine the perceptions and learning motivation of grade 2019 students more broadly and deeply about the learning process at the Faculty of Medicine of Pattimura University in 2019. This research is a descriptive study with a cross-sectional approach. The sample collected was 150 people using total sampling technique. Retrieval of data using a questionnaire. Perception frequency distribution of grade 2019 students at the Faculty of Medicine of Pattimura University Ambon regarding the learning process from teacher centered learning to student centered learning, the perception shown is very good as many as 109 people (72.6%) and good perceptions as many as 40 people (26.7%), many problems as much as 1 person (0.7%). Students with moderate learning motivation was 27 people (18.0%), high motivation was 123 people (82.0%).